Irish-UK services trade and Brexit - Martina Lawless (The Economic and Social Research Institute (ESRI), 2018)
This paper examines the determinants of international trade in services using data on total services trade and a breakdown of the component subsectors between 28 reporting countries and over fifty partner countries. Using a gravity model approach, we find that the income level and size of the trading partners and the distance between them affect trade flows in services in a similar manner to trade in goods. In the context of Brexit, we focus on the degree to which the European Union has facilitated trade in services amongst its members compared to trade between other partner countries. EU membership is found to be associated with an overall 26% higher level of trade in services. Furthermore, across the subsectors we find considerable variation in the degree to which EU membership impacts trade flows, ranging from being statistically insignificant or even slightly negative to having positive effects equivalent to a more than doubling of trade. We then relate these findings to potential impacts of Brexit on services trade between Ireland and the UK. Assuming that exiting the EU has symmetric effects to membership, Irish services imports from the UK could decline by 33% and exports almost half in this scenario, driven mainly by reductions in the insurance and telecommunications sectors. In terms of overall services trade, this is equivalent to a 3.5% reduction in imports and a 9% fall in exports, although this estimate does not take account of any potential increases in trade with other countries or policy actions to mitigate the effects of the UK exit from the EU.
Keywords: 330